A soft on/off switch based on the electrochemically reversible H–J interconversion of a floating porphyrin membrane. Issue 30 (6th July 2021) - Molina-Osorio, Andrés F.; Yamamoto, Sho; Robayo-Molina, Iván; Gamero-Quijano, Alonso; Nagatani, Hirohisa; Scanlon, Micheál D.
Abstract : The structural rearrangement of a porphyrin membrane self-assembled at a "soft" liquid|liquid interface from a H- to J-molecular configuration is reversibly modulated by externally manipulating the interfacial Galvani potential difference. Abstract : Soft molecular assemblies that respond reversibly to external stimuli are attractive materials as on/off switches, in optoelectronic, memory and sensor technologies. In this Edge Article, we present the reversible structural rearrangement of a soft porphyrin membrane under an electrical potential stimulus in the absence of solid-state architectures. The free-floating porphyrin membrane lies at the interface between immiscible aqueous and organic electrolyte solutions and is formed through interfacial self-assembly of zinc(ii ) meso -tetrakis(4-carboxyphenyl)porphyrins (ZnPor). A potential difference between the two immiscible electrolyte solutions induces the intercalation of bis(triphenylphosphoranylidene)ammonium cations from the organic electrolyte that exchange with protons in the porphyrin membrane. In situ UV/vis absorbance spectroscopy shows that this ionic intercalation and exchange induces a structural interconversion of the individual porphyrin molecules in the membrane from an H- to a J-type molecular configuration. These structural rearrangements are reversible over 30 potential cycles. In situ polarisation-modulation fluorescence spectroscopy further provides clear evidence of structural interconversion of the porphyrin membrane, as intercalation of the organic electrolyte cations significantly affects the latter's emissive properties. By adjusting the pH of the aqueous phase, additional control of the electrochemically reversible structural interconversion can be achieved, with total suppression at pH 3.